Salienz und System - Glauninger, Manfred Michael (Linguistik Online, 2014)
The object of investigation in this paper is the linguistic conception of salience by focusing its still predominantly essentialistic, only in modest approaches constructivistic, modelling. This indicates one of the most basic methodological desiderata of linguistics: the discussion and revision of its systemic foundation. Therefore, the aim of this article is to initiate a decidedly constructivist discussion of linguistic salience, and its adaption and transformation, respectively. This could result in an exponentiated connectivity of (post-)modern constructivistic sociolinguistics to advanced self-referential autopoietic positions of systems theory.